2011
DOI: 10.1016/j.avsg.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Does a Contralateral Carotid Occlusion Adversely Impact Carotid Artery Stenting Outcomes?

Abstract: Background Carotid artery stenting (CAS) has grown as a possible alternative for the treatment of extracranial cerebrovascular disease in the past decade. A pre-existing contralateral carotid artery occlusion has been described as a risk factor for inferior outcomes following carotid endarterectomy (CEA), yet its impact on CAS outcomes is less understood. Methods Retrospective review of 417 CAS procedures from May 2001 through July 2010 at a single center using self-expanding nitinol stents and mechanical em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 13 publications
0
32
0
4
Order By: Relevance
“…Although several reports have confirmed that contralateral carotid occlusion does not adversely affect CAS [22][23][24] , previous studies have shown conflicting results regarding the perioperative risk of the patients with contralateral ICA occlusion undergoing CEA 22,24,[27][28][29][30][31] . Antoniou et al conducted a systematic review, and showed contralateral occlusion increases the incidence of perioperative strokes 27 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although several reports have confirmed that contralateral carotid occlusion does not adversely affect CAS [22][23][24] , previous studies have shown conflicting results regarding the perioperative risk of the patients with contralateral ICA occlusion undergoing CEA 22,24,[27][28][29][30][31] . Antoniou et al conducted a systematic review, and showed contralateral occlusion increases the incidence of perioperative strokes 27 .…”
Section: Discussionmentioning
confidence: 94%
“…One of the problems of this strategy is the higher incidence of post procedural hemodynamic complications. Although contralateral carotid occlusion does not adversely impact CAS [22][23][24] , there have been no reports indicating that CAS is safer in patients with contralateral severe ICA stenosis than is CEA. Rather, we think that hypotension after CAS for the asymptomatic side may be dangerous for the symptomatic hemisphere, because CAS for the asymptomatic side usually does not improve hemodynamics in the symptomatic cerebral hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…PAD was associated with a 1.6-to 2-fold increased risk of mortality and was found in up to 44% of patients. Finally, with regard to contralateral carotid occlusion, we extended data from Keldahl et al 7 who found a slight but not significant increase of mortality during a mean follow-up of 4 years in patients undergoing CAS with contralateral carotid occlusion. In our derivation but not in our validation cohort, contralateral occlusion was associated with a 1.7-fold increased risk of mortality.…”
Section: Discussionmentioning
confidence: 78%
“…So far, single risk factors such as medical high risk, diffuse proliferative hyperplasia after CAS, diabetes mellitus, low high-density lipoprotein cholesterol levels, low body mass index, and contralateral carotid occlusion have been described but no comprehensive risk assessment has been performed. [3][4][5][6][7] The identification of a comprehensive risk profile determining mortality in this high-risk population with advanced age and high probability of generalized atherosclerotic disease is of particular clinical interest, specifically if reversible risk factors are included in the risk profile and late outcome may be improved by their treatment. A comprehensive risk management may be of particular relevance for patients with asymptomatic carotid stenosis in whom competing risks are more likely to impact late outcome.…”
mentioning
confidence: 99%
“…On the other hand, they thought that CAS would be better for the first revascularization procedure than CEA because CCS would adversely affect CEA. 17,18 Although CCO does not adversely impact CAS, [29][30][31] there have been no reports indicating that CAS is safer in patients with contralateral severe ICA stenosis than is CEA. In fact, contralateral occlusion is one of the risk factors in Protected…”
Section: Discussionmentioning
confidence: 97%